Estudio de prefactibilidad para la producción de un sazonador a base de zapallo loche (Cucurbita moschata) - Acosta Davila, Miguel Alberto (2023)
The objective of this research was to evaluate the commercial, technical, economic and financial viability of the production of a seasoning based on pumpkin loche, this due to the growth in demand for industrialized products with a culinary and gastronomic origin that provides a flavor and aroma unique to Peruvian gastronomic dishes. Therefore, a market study is carried out in relation to the demand, supply, price, size and location of the plant, where the city of Lima was chosen for the macro location, while in the micro location the city of Lima was chosen. Lurin district. In addition, being a new, unique and innovative product, a marketing plan will be needed that allows the recognition of the product, and thus be purchased in supermarkets and markets in the city of Lima. The capacity of the plant will be determined by the peeling-washing process, being 108643,32 kg/year, likewise, 10 machines, 29 workers for the entire organization and a total area of 731,25 m2 are required. Likewise, you need an investment of S/ 1,399,066,62 and working capital for the first two months of operation of S/ 384,166,75. Finally, according to the financial evaluation, there will be a NPV of S/1,414,489,26, IRR of 67,42%, a recovery period of 1,78 years, so it is concluded that the project is profitable.